Competitive victimhood as a lens to reconciliation: An analysis of the black lives matter and blue lives matter movements. (1st July 2019) - Solomon, Johanna; Martin, Adam
Abstract: Literature on intergroup conflict and identity is well established; this literature includes work on competitive victimhood—the process by which groups attempt to establish that they have suffered more than opposing groups (Noor et al., Personality and Social Psychology Review, 2012, 16(4), 351–374) to restore feelings of moral identity, or cache often for use in a political context (Sullivan et al., Journal of Personality and Social Psychology, 2012, 102(4), 778). Within prior work on competitive victimhood, models of reconciliation based on the particular needs and identities established within the competitive victimhood dynamic have also been posited (SimanTov‐Nachlieli et al., European Journal of Social Psychology, 2015, 45(2), 139–145; Shnabel et al., Journal of Experimental Social Psychology, 2013, 49(5), 867–877). While competitive victimhood theory has been applied in prior work to several cross‐national settings, there exist other important areas of intergroup tension that have not been explored. We propose that the concept of competitive victimhood can be fruitfully used to understand movement‐countermovement dynamics, including those related to conflictual race relations in the United States. Specifically, this article will examine the dynamic between the movements "Black Lives Matter" and "Blue Lives Matter" as a salient paired research case of a movement and countermovement for investigating identity and victimhood. In our present article, we map the discourse of the Black and Blue Lives Matter movements as illustrations of collective victimhood (Schori‐Eyal et al., Journal of Applied Social Psychology, 2014, 44(12), 778–794) and competitive victimhood (Noor et al., Personality and Social Psychology Review, 2012, 16(4), 351–374). We find that while both movements demonstrate competitive victimhood, they are also qualitatively different. Due to differences in threat, power, and history of those the movements advocate for, each movement demonstrates different needs (Burton, Conflict: Human needs theory, Springer, 1990). We posit that the identity dynamics of competitive victimhood within social movements specifically lead to important and different identity needs for agency and morality (Shnabel & Noor, in Restoring civil societies: The psychology of intervention and engagement following crisis (pp. 192–207), Wiley‐Blackwell, Chichester, England, 2012). We examine what these differences would mean in these particular movements, as well as for potential avenues of community building based on addressing these needs. In all cases, we aim to show that what has largely been considered a criminal justice phenomenon in the United States is fundamentally political, with roots and possible solutions in intergroup identity dynamics that can be fruitfully explored within political psychology.